Simulation Based Analysis of 150° Conduction Mode and SPWM Technique for Three Phase Voltage Source Inverter - Dipenkumar H. Kambaliya; Samir P. Darji (International Journal of Engineering and Management Research, 2022)
This paper presents Simulation based analysis of 150° conduction mode and SPWM technique for three phase voltage source inverters. Better conduction mode is consisting more levels of output voltage. Different simulations results of conduction mode and SPWM using PSIM 6.0 software is analysts. Methods are compared on the basis of number of switches, number of levels of voltage and total harmonic distortion.